Analisis Analisis Nilai Tambah Pengolahan Belut Menjadi Keripik Belut di Desa Kedu Kabupaten OKU Timur. : Keripik belut - muridin, Muridin; Atika (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2025)
Summary. Research in 2024. Analysis of Added Value of Eel Processing into Eel Chips (Case Study) in Kedu Village, Buay Madang Timur District, East OKU Regency. The location research was conducted intentionally (purposive). Respondents were eel chip home industry actors in Kedu Village, Buay Madang Timur District, East OKU Regency. Based on the results and discussions of the research that has been carried out, the following conclusions can be drawn: Income in the eel processing business into eel chips in Kedu Village is IDR 45,942 / PP. The added value generated in this business is IDR 560,192 / PP and 56,019 / Kg. The eel processing business into eel chips is profitable to develop in Kedu Village, Buay Madang Timur District with several indicators, namely the R / C ratio of 1.69. BEP Price of IDR 74,006 / Kg, and BEP Production of 0.13 kg